2010
DOI: 10.1523/jneurosci.5389-09.2010
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Depletion of Descending Serotonin Unmasks Its Novel Facilitatory Role in the Development of Persistent Pain

Abstract: Recent studies indicate that persistent pain after tissue or nerve injury is accompanied by an enhanced net descending facilitatory drive that contributes to an amplification and spread of pain. Although 5-HT-containing neurons in the rostral ventromedial medulla (RVM) provide the major descending serotonergic projection to the spinal cord, it is not clear whether the neurotransmitter 5-HT itself released from RVM-spinal neurons contributes to descending pain modulation. In the present study, we determined the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

18
181
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 180 publications
(200 citation statements)
references
References 72 publications
18
181
0
Order By: Relevance
“…[24][25][26] By contrast, pro-inflammatory and anti-inflammatory cytokines, such as interleukin-1, play crucial roles in the establishment and maintenance of neuropathic pain. 27) Tricyclic antidepressants reportedly inhibited the release of interleukin-1 in mixed glial and microglial cell cultures from rats.…”
Section: Discussionmentioning
confidence: 99%
“…[24][25][26] By contrast, pro-inflammatory and anti-inflammatory cytokines, such as interleukin-1, play crucial roles in the establishment and maintenance of neuropathic pain. 27) Tricyclic antidepressants reportedly inhibited the release of interleukin-1 in mixed glial and microglial cell cultures from rats.…”
Section: Discussionmentioning
confidence: 99%
“…www.intechopen.com Therefore, it is concluded that 5-HT derived from descending fibers from the RVM activated spinal/trigeminal dorsal horn neurons via 5-HT3 receptors and facilitated pain behavior (Okamoto et al, 2005b). Recently, Wei et al (2010) showed the essential role of 5-HT in this system in pathological pain conditions by selectively blocking 5-HT production in the RVM. As for 5-HT2A receptors, we demonstrated that this receptor subtype is involved in the suppression of nociceptive processing and behavior using the deep craniofacial pain model (Okamoto et al, 2007).…”
Section: Descending Facilitation Mediated By 5-ht and 5-ht3 Receptorsmentioning
confidence: 99%
“…The resulting depression, anxiety, sleep fragmentation, allodynia, and hyperalgesia characterize a number of chronic pain disorders. [2][3][4][5][6][7][8][9][10][11][12][13] At least two etiological pathways are posited for central sensitization. The first is chronification of nociceptive pain; and involves neuroplastic changes, and peripheral sensitization as precursors to central sensitization and the resulting clinical pain.…”
Section: What Is Central Sensitization (Cs)mentioning
confidence: 99%
“…[13] Many of the drugs that we use to address central sensitization will have a beneficial effect on the ability of the patient to cope with the pain, as well as to diminish the central sensitization itself. [1,2,8,9,13,41,45] Drugs used to address the effects of central sensitization:…”
Section: Therapymentioning
confidence: 99%
See 1 more Smart Citation